Using rankings to evaluate genetic performance and gain across space and time - 1000FARMS Platform (2025)
This poster showcases how data collected through the tricot approach can be used to estimate genetic gain in crop breeding programs. It explains the assumptions, methods, and implications of calculating genetic gain from decentralized on-farm testing. The work, developed as part of the 1000FARMS Platform project, highlights how integrating farmer-generated data can support more responsive and adaptive breeding decisions.